Éducation au développement durable : intérêts et limites d’un usage scolaire des investigations multiréférentielles d’enjeux - Jean-Marc Lange (Éducation et Socialisation)
Education for Sustainable Development (ESD) has been developed in recent years from a dual process of recommendation: the international incentive texts, and the national texts of guidance and prescription. They base their social legitimacy, specified in a recent French law (July 2013): it is a "moral and civic" education focused on stakes. For many authors, these societal issues, the objects of this education, require a global and complex approach opposed to an analytical, reductionist and scientist approach, or that they betray the ideal the acquisition of knowledge in favor of a utilitarian drift. It is these tensions that this article proposes to examine in some registers - epistemological, educational, curriculum and teaching - with a view to clarifying and overcoming them, especially by means of an approach, adapted to the compulsory education, the “multireferential” investigation of stakes.